FAKTOR PEMANFAATAN LAYANAN TERKAIT PELAYANAN KESEHATAN UNTUK REMAJA DENGAN KEHAMILAN REMAJA - Silfia Nuzulus Sa'idah (Journal of Midwifery Tiara Bunda, 2023)
Background:In Indonesia, according to the latest survey by the Central Statistics Agency (BPS) through the Indonesian Demographic and Health Survey (IDHS), in 2012 the teenage pregnancy rate in the 15-19 year age group reached 48 out of 1,000 pregnancies (SDKI, 2012). Objective: To determine the relationship between the use of adolescent reproductive health and teenage pregnancy. The research method used was a designunparalleled case control study which is a retrospective observational analytic epidemiological study. The number of samples is 142 respondents, consisting of 71 cases and 71 controls. Method: Sampling using proportional random sampling. The data analysis used was univariate and bivariate analysis using the chi-square test, and multivariate analysis using logistic regression. RESULTS: showed that there was a significant relationship between PKPR utilization and teenage pregnancy (p=0.002, OR: 3.552, CI: 95%), there was a significant relationship between the level of knowledge about reproductive health and teenage pregnancy (p=0:01, OR: 3.254, CI: 95%), there is a significant relationship between the level of knowledge about PKPR and teenage pregnancy (p = 0.019, OR: 2.233, CI: 95%), there is a significant relationship between parental income and teenage pregnancy (p = 0.029, OR : 2.119, CI: 95%), there is a significant relationship between father's education and teenage pregnancy (p = 0.006, OR: 2.706, CI: 95%). Conclusion PKPR utilization factor has the most dominant influence on teenage pregnancy in Tangerang.